Sirrul asrar (book review) - Abdul Razak (Reviewer), Mohd Abbas (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
Overview of the Book: The book deals with many Islamic Sufi teachings and practices. The author, As-Syeikh Abdul Qadir Al-Jailani (1077-1166) is a great Sufi scholar who hails from Persia, presently known as Iran.In his book the author explains many issues with regard to Ibadah viewed from the Syariah and Tariqat perspectives. Written in the Sufi way, the book has a blend of philosophy, metaphysics and religion (Islam) in it. Sometimes it is difficult for a reader to differentiate the information as to whether it is the religious teaching of Islam or a philosophical idea. Among other things the book engages its readers in discussing whether is it possible to have a vision through the (Basyirah Batin/eye of the heart) of Allah in this worldly life, disciplining of the Nafs (the human self), the concept of happiness and misfortune, who is a Fakir (the one dependent on Allah), Cleanliness, Solat (Prayer), Fasting (Saum) Charity(Zakah), Pilgrimage (Haji), Religious Seclusion (Khalwah& Uzlah), Sleep & Dream interpretation, etc. The great passion that has gone into producing this work raises a crucial question as to whether it was written by the Great Syeikh or by his disciples, upon the demise of the master. It looks as though many things were written in an exaggerated way by his disciples, perhaps a recollection of ideas communicated to them by the master.